Spontaneous Duodenal Perforation as a Complication of Kawasaki Disease - Kambiz Masoumi; Arash Forouzan; Hossein Saidi; Hazhir Javaherizadeh; Ali Khavanin; Mohammad Bahadoram (Case Reports in Pediatrics)
Kawasaki disease is generally known as a systemic vasculitis that often concerns doctors due to its serious cardiac complications; however, other visceral organs may get involved as well. Surgical manifestations of the intestinal tract in Kawasaki disease are rare. In this report, we describe the case of a 2.5-year-old boy with typical Kawasaki disease who presented with GI bleeding and surgical abdomen. The diagnosis of duodenal perforation was confirmed.